Islamic business ethics in Muslim fashion store: A study at 3 Nur Shop, Pattani, Thailand - U-Mar, Nurainee; Andriansyah, Yuli; Hattabou, Anas (Universitas Islam Indonesia, 2024)
Introduction The integration of Islamic business ethics into entrepreneurship is critical in predominantly Muslim societies. This study examines the implementation of these ethics at the 3 Nur Shop, a Muslim-owned convection business in Pattani, Thailand. The study highlights how adherence to ethical principles can influence business performance and community perceptions.Objectives This research aims to analyze the application of Islamic business ethics—based on the principles of Shiddiq (honesty), Amanah (trustworthiness), Fathanah (wisdom), and Tabligh (communication)—in the operations of 3 Nur Shop and to evaluate its social and economic contributions to the local community.Method The study employs a mixed-methods approach. Quantitative data were gathered from the shop’s employees to assess ethical adherence in daily operations, while qualitative data were collected from customers to understand their perceptions and experiences with the shop.Results Findings indicate that 3 Nur Shop practices Islamic business ethics comprehensively. Honesty is reflected in clear product information, trustworthiness in fulfilling customer expectations, wisdom in business innovation, and effective communication in maintaining customer relationships. These practices foster trust, enhance customer loyalty, and contribute to sustainable business growth.Implications The study emphasizes the importance of incorporating ethical practices in Muslim-owned businesses as a strategy for achieving commercial success while adhering to religious values. It provides a framework for entrepreneurs to integrate moral principles into their operations, fostering both ethical compliance and customer satisfaction.Originality/Novelty This research contributes to the literature by presenting a practical case study of Islamic business ethics implementation. It demonstrates how these principles can create a competitive advantage and build community trust, offering valuable insights for businesses in predominantly Muslim regions.